2017
DOI: 10.1515/jvetres-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Epizootic and epidemiological situation of Trichinella sp. infection in Poland in 2006–2015 in view of wild boar population dynamics

Abstract: IntroductionThe objective was to evaluate the epizootic and epidemiological situation of Trichinella sp. infection in Poland between 2006 and 2015 against the dynamics of the wild boar population and its primary reservoir host.Material and MethodsBoar and porcine trichinosis epizootic analysis was based on General Veterinary Inspectorate data from RRW-6 bulletins. The epidemiological situation was evaluated on the basis of the data supplied by the Department of Epidemiology of the National Institute of Hygiene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…While the results of this study are not directly comparable with those from other countries due to different sampling and study designs, it is clear that Trichinella parasites thrive in the region. The prevalence in wild boars in this study was lower than that observed in Latvia [ 20 ], but higher than that in Poland [ 21 ]. The prevalence in brown bears and lynxes was higher than that in Finland [ 22 ], while the prevalence in lynxes was lower than that in Latvia [ 8 , 23 ].…”
Section: Discussioncontrasting
confidence: 83%
“…While the results of this study are not directly comparable with those from other countries due to different sampling and study designs, it is clear that Trichinella parasites thrive in the region. The prevalence in wild boars in this study was lower than that observed in Latvia [ 20 ], but higher than that in Poland [ 21 ]. The prevalence in brown bears and lynxes was higher than that in Finland [ 22 ], while the prevalence in lynxes was lower than that in Latvia [ 8 , 23 ].…”
Section: Discussioncontrasting
confidence: 83%
“…On the contrary, in Poland (to the north of Slovakia) the animal Trichinella infection is more prevalent and has been detected not only in red foxes and wild boars, but also in pigs. During the 10-year study period (2006-2015), infection was detected in 282 pigs and in 0.51% of 1,012,021 wild boars [32]. In this country, the presence of all three species occurring also in Slovakia has been recorded.…”
Section: Seropositivity To Trichinella In Voluntary Respondentsmentioning
confidence: 86%
“…Currently, the main risk to humans is associated with the consumption of wild boar meat, due to the high prevalence of Trichinella spp. in these animals, reaching 0.5% [3,4].…”
Section: Of 11mentioning
confidence: 76%